2017
DOI: 10.1111/nyas.13473
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in using fluorescence tagging of nanomaterials: tecto‐dendrimers in skin tissue as investigated by Cluster‐FLIM

Abstract: Targeted topical application promises high drug concentrations in the skin and low systemic adverse effects. To locate drugs and drug-delivery systems like nanocarriers, fluorescent dyes are commonly used as drug surrogates or nanocarrier labels in micrographs of tissue sections. Here, we investigate how labeling degree, concentration of fluorophore, and nanocarrier may affect the interpretation of these micrographs. False-negative penetration results due to inter- and intramolecular quenching effects are like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Yet, it does not discriminate between the various barriers of the skin. Combining this technique with microscopical techniques can visualize local concentrations of the dye [ 33 , 152 ] (see also Section 3.2 ).…”
Section: And How Can We Measure Them?mentioning
confidence: 99%
“…Yet, it does not discriminate between the various barriers of the skin. Combining this technique with microscopical techniques can visualize local concentrations of the dye [ 33 , 152 ] (see also Section 3.2 ).…”
Section: And How Can We Measure Them?mentioning
confidence: 99%
“…Figure 4 B–D visualizes DL skin penetration using FLIM, providing a spatially resolved image of DL distribution in the tissue (Figure 4 D). Cluster‐FLIM enhances the image contrast as well as statistical significance, [5d, 8] thereby resolving detailed skin structures (Figure 4 D). The highest DL concentration is depicted by the red fluorescence decay cluster in the false‐color coded image with the fastest fluorescence decay time, while the lowest concentration is shown in blue with the slowest fluorescence decay time (Figure 4 D, E).…”
Section: Resultsmentioning
confidence: 99%
“…where IROI is the fluorescence intensity in the region of interest (ROI), such as whole skin, viable epidermis or dermis, MW is the molecular weight, and α and b are slope and intercept of a linear fit of the concentration calibration data (Figure S18) with b=0 for Equation (1). The FLIM lifetime data were analyzed by a cluster algorithm, [5d, 8] which allows us to separate image pixel according to discrete lifetime clusters. We calculated the concentration from the lifetime data using Equation 2: truecDL()τ=cluster()τcluster-bα×#pixelclustertotal4pt#pixel4ptin4ptROI×MW×Fr, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to chemotherapy and gene delivery applications, CSTDs can also be shaped toward the applications in biological imaging. As an example, Volz et al 44 reported the use of G5/G2.5 CSTDs for fluorescence imaging of the interaction of nanocarriers with skin. First, the G5/G2.5 CSTDs were synthesized and then fluorescently labeled with a dye of fluorescein isothiocyanate (FITC).…”
Section: Biomedical Applications Of Cstdsmentioning
confidence: 99%